Neoadjuvant Treatment for Resectable and Borderline Resectable Pancreatic Cancer: Chemotherapy or Chemoradiotherapy? - Versteijne, Eva; de Hingh, Ignace H. J. T.; Homs, Marjolein Y. V.; Intven, Martijn P. W.; Klaase, Joost M.; van Santvoort, Hjalmar C.; de Vos-Geelen, Judith; Wilmink, Johanna W.; van Tienhoven, Geertjan (Frontiers in Oncology, 2022)
Worldwide, there is a shifting paradigm from immediate surgery with adjuvant treatment, to a neoadjuvant approach for patients with resectable or borderline resectable pancreatic cancer (RPC or BRPC). Comparison of neoadjuvant and adjuvant studies is extremely difficult because of a great difference in patient selection. The evidence from randomized studies shows that overall survival by intention to treat improves after neoadjuvant gemcitabine based chemoradiotherapy or chemotherapy (various regimens), as compared to immediate surgery followed by adjuvant chemotherapy. Radiotherapy appears to play an important role in mediating locoregional effects. Yet, since more effective chemotherapy regimens are currently available, in particular FOLFIRINOX and Gemcitabine/Nab-paclitaxel, the optimal chemotherapy regimens for neoadjuvant treatment are not established. Future randomized trials should combine these multi agent regimens with (for instance stereotactic) radiotherapy to further improve outcomes of RPC and BRPC.